Matching Skills and Jobs in Estonia - Demmou, Lilas (OECD Economics Department Working Papers, 2012)
The labour market in Estonia is volatile, increasing the risk that groups with some obstacles to enter the labour market (youth, non-Estonian speakers and workers with no upper secondary graduation certificate) may become long-term unemployed, due to the aggravating skills mismatch in the wake of structural change. Avoiding a permanent exit from the labour force makes a multi-pronged strategy necessary, including strengthening activation policies, a better school-to-job transition, improving the cooperation with employers to improve vocational training programmes, stepping up targeting life-long learning support, and improving the access of tertiary studies for students from weak social backgrounds